ANALISIS KEKERINGAN HIDROLOGI BERDASARKAN METODE NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) DI DAERAH ALIRAN SUNGAI ALANG KABUPATEN WONOGIRI - Mochammad Fajar Fadlillah; Rintis Hadiani; S Solichin (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2018)
Drought was yearly disaster which often happen at region of Indonesia. In this reseaech, we observe in Wonogiri especially Alang Watershed, located at southwest of Wonogiri dam and between Plumbon and Serenan district. The purpose of this research is to find the value of drought index using Normalized Difference Vegetation Index (NDVI). The drought is detected by using the debit. So, then created the relations of drought index and debit. Next, mapping the drought area in Alang watershed using software ArcGIS.Collecting data is the first step of this research., then analyze the data and doing validation test using RAPS method. Calculating the rain area using polygon thiessen. NDVI value is obtained from processing the Landsat 7 and 8 image with Arcgis. Classifying NDVI value based on Peraturan Menteri Kehutanan RI nomor P.12/Menhut-II/2012. Calculating debit using NRECA. Then, creat the relation chart between drought index and debit. Mapping the drought area from the month which had lowest NDVI value and had lowest debit. Also mapping the drouht from 2008-2017.knowing the drought area in Alang watershed and knowing the realtion chart between drought index and debit are the purpose of this research. The result showed that the relation chart of drouht index and debit aren’t good to detecting the debit. The distribution of drought area is obtained from processing the Landsat 8 image with variative distribution and more accurate result.